2021
DOI: 10.3390/ma14040715
|View full text |Cite
|
Sign up to set email alerts
|

Sizing and Topology Optimization of Trusses Using Genetic Algorithm

Abstract: Genetic algorithms are a robust method for a solution of wide variety optimization problems. It explores a big space of design variables in order to find the best solution. From the point of view of a user, the algorithm requires the encoding of design variables into the form of strings and the procedure of optimization uses them for optimization. Here, for the structural engineer, it is crucial to find the form of objective function including the constraints of the task and also to avoid critical states durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In this respect, it has been found that, despite the rapid developments in computing technology, the demands associated with computational costs and time constraints relating to the use of resources in the field of structural analysis do not preclude them. This situation arises due to the constant growth in the requirements for accuracy and therefore complexity of analytical models (Bocko [3], Delyová et al [4]).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, it has been found that, despite the rapid developments in computing technology, the demands associated with computational costs and time constraints relating to the use of resources in the field of structural analysis do not preclude them. This situation arises due to the constant growth in the requirements for accuracy and therefore complexity of analytical models (Bocko [3], Delyová et al [4]).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, much research explores the possibility of using genetic algorithms in order to optimize the designed structures of various materials [16][17][18]. In the case of steel structures, they are mostly used for topology optimization to generate innovative lightweight rod structures with interesting and efficient rods configurations that are difficult to obtain in a conventional way [19]. Topological optimization of trusses, steel frames, and grid structures is described in many publications.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively simple assumptions used to determine stresses found in truss members make it possible to apply various techniques and algorithms to optimise their shape [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. The popularisation of numerical methods, as well as the availability of CAD software have facilitated the design process for systems based on lattice beams [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%